Prognostic factors in 291 patients with pulmonary metastases submitted to thoracotomy - Rossi, Benedito Mauro (1995)
Pulmonary metastases are among the most common sites for the spread of cancer, particularly with mesenchymal tumors. Despite improvements in cancer therapy, the prognosis remains poor, except for the highly selective group of patients who are considered eligible for surgical treatment and those with chemosensitive tumors. The main objective of this study was to evaluate survival results of 291 patients who underwent thoractomy due to pulmonary metastases between 1953 and 1986. The number of metastases ranged from a minimum of 1 to as many as 30. The type of resection depended on site, size, and number of pulmonary lesions: 154 wedge resections, 49 lobectomies, and 9 pneumectomies. The tumor was not resectable in the remaining 79 patients. Of the prognostic factors analyzed, only type of pulmonary resection (wedge vs. lobectomy vs. pneumectomy vs. unresectable) and disease free interval (DFI) between primary treatment and pulmonary metastases diagnosis ( <=6 months vs. 7-12 months vs. >12 months) were selected as independent predictors of the risk of death in multivariate analysis. A reduced model for bone tumors included disease free interval, sex and histology.